ENCULTURATION OF TRADITIONAL MADURA FOOD: FROM TAJIN SOBIH SELLERS TO SPATIAL ACTIVITY IDEAS IN MATHEMATICS - Chusna, Noril Lailatul; Wardhani, Indah Setyo; Syauqina, R. A. Qothrun Nada; Ulfa, Sukriya; Fijriyah, Izzah (Jurnal Pendidikan Matematika (JUPITEK), 2024)
The purpose of this study is to explore the ideas of spatial skills activities in mathematics from tajin sobih culture. Spatial skills are one of the important skills used to help solve problems in the real world. Exploring spatial ideas in tajin sobih culture can be useful in learning geometry and mathematics. This research uses qualitative research methods with the researcher as a participant. The collection techniques in this study were obtained through observation and in-depth literature review. The data analysis technique used includes four main processes, including data collection through literature and documentation, data reduction, data presentation in the form of narrative text, and conclusion drawing. This research produced spatial skills activity ideas and mathematical ideas, especially in the field of geometry of flat and spatial shapes from the tajin sobih culture through the making process to the presentation process. Other mathematical ideas are number and measurement. Based on the results of the research, it was found that the shape of the tajin sobih container is hemispherical, the wooden ladle has a length that can be measured using standard units such as cm, tampah or woven basket is circular, and so on